EFEKTIVITAS LAYANAN SKCK ONLINE DALAM MEWUJUDKAN PELAYANAN PUBLIK DI PORLES KARAWANG - Rahman, Dicky Fadlika (Advances in Police Science Research Journal, 2020)
The development of technology in the current era, makes many people must be able to follow it. Likewise in the community service sector in the Police Sector. There are still many service processes in the Police field that are of a conventional nature such as in the making of Police Records Certificate (SKCK). E-SKCK service is expected to be able to provide a more comfortable, transparent and clean service pattern while also following the established procedures. In accordance with Pasal 14 Huruf K Undang-Undang Nomor 2 Tahun 2002 concerning the function of the state government to provide the best possible service to the public. The purpose of this study is to provide a pattern and positive picture of the implementation of the service system by SKCK Online. Through descriptive analysis method, then there will be a simple observation of the data, then the results of this data will later be analyzed to get responses from the community and also the efficiency of the use of online service systems. From this research, it is hoped that the public will become more aware of technological advancements, especially in the E-SKCK manufacturing service process that provides excellent effectiveness in terms of time and transparency without going through compromising brokers. Then, with the ability of officers or qualified members, it will be an encouragement for the creation of safe and comfortable community services and is assisted by the existence of a good network of Karawang area intelligence.